ANALISI DAMPAK SOSIAL AKIBAT KEBIJAKAN JAMINAN PRODUK HALAL (KOMPARASI PERSEPEKTIF HUKUM FIKIH DAN HUKUM POSITIF)Dampak Sosial Kebijakan Jaminan Produk Halal: Analisis Hukum Islam dan Hukum Positif - Najiburrahman, Moh.; Rozak, Fakih Abdul (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Institut Agama Islam Negeri Sultan Amai Gorontalo, 2025)
Food products, beverages, medicines, cosmetics, genetically modified products and biological chemical products whose halalness is guaranteed are the most important factors for consumption among Muslim communities in particular. The purpose of the research is to find out whether the guarantee of halal products by the state can have a positive social impact in protecting the rights to comfort, security and safety of consumers who use these products. This research is a field and literature study with data sources in the form of interviews and literature. Data sources in the form of interviews and literature. The data obtained is analyzed by descriptive qualitative with the approach of Islamic law and positive law. The results showed: first, halal product guarantees have a positive impact on MSME actors and provide protection for consumers who consume products circulating in the market; second, Islamic law and positive law very clearly show the importance of halal guarantees for products that will be used and consumed by the community, especially the Muslim community.